Existence and Uniqueness of Homoclinic Solution for a Class of Nonlinear Second-Order Differential Equations. (25th December 2012) - Chen, Lijuan; Lu, Shiping
Abstract : The authors study the existence and uniqueness of a set with2 k T -periodic solutions for a class of second-order differential equations by using Mawhin's continuation theorem and some analysis methods, and then a unique homoclinic orbit is obtained as a limit point of the above set of2 k T -periodic solutions.